Adsorption of Hexavalent Chromium Ion from Aqueous Solution by Sodium Alginate and Carboxymethyl Cellulose Beads: Kinetics and Isotherm Studies - Salim, Ali J (Al-Nahrain Journal of Science, 2018)
The removal of hexavalent chromium from aqueous solutions using biopolymeric beads of crosslinked sodium alginate (SA) and carboxymethyl cellulose (SCMC) as the adsorbent is reported in this paper. The biopolymeric alginate and carboxymethyl cellulose beads were prepared and characterized by FTIR spectra. The studies of adsorption of Cr(VI) were conducted by varying various parameters: such as contact time, pH, amount of adsorbent and concentration of adsorbate. A comparison of kinetic models applied to the adsorption of Cr(VI) ions on the adsorbents was evaluated for the pseudo-first-order, the pseudo second-order and intraparticle diffusion kinetic models respectively. Results show that the pseudo second-order kinetic model was found to correlate the experimental data well. The experimental equilibrium data were applied to Langmuir and Freundlich isotherm models and their equilibrium parameters were estimated.